Narrowing of band gap and decrease in dielectric loss in La1-xSrxMnO3 for x = 0.0, 0.1, and 0.2 manganite nanoparticles - Ali, Akhtar; Shah, Wiqar H.; Ullah, Zakir; Malik, Shaheryar; Rauf, Muhammad; Askar, Sameh; Imran, Naveed; Ahmad, Hijaz (Frontiers in Materials, 2024)
Lanthanum strontium manganite's polycrystalline (La1-xSrxMnO3, LSMO) compounds are rich in electronic storage devices due to their minimum losses and electronic charge transport property. In this study, we have investigated how varying substitutions of Sr 2+ for x= 0.0, 0.1, and 0.2 ascribed to the tuning of the optical band gap with dielectric losses in La1-xSrxMnO3 nanoparticles. Synthesized samples are structurally analyzed by X-ray diffraction. A rhombohedral R3 ̅ 𝑐 crystal structure confirmed for all prepared samples along with crystallite size ranging from 15 nm to 20 nm was estimated with other lattice parameters. Polygonal or hexagonal-like morphology revealed by field emission scanning electron microscopy with moderate size distribution of nanoparticles affected by thinner grain boundaries in doped LSMO. The Energy Dispersive Spectroscopy was employed to confirm the elemental composition in a compound and the Infrared Spectrum showed bonding in the fingerprint region It was observed that there was a significant reduction in the optical band gap, which was measured using Ultraviolet spectrometer absorption data. The band gap decreased from 4.34 eV to 4.11 eV. This reduction was found to be related to the difference in refractive index, which was calculated using both Moss and Herve-Vandamme relations. In parallel, the frequency-dependent dielectric analysis revealed that an increase in Sr content was proportional to the frequency, inversely affecting the dielectric loss. Moreover, the AC conductivity of the prepared samples was increased with the rise in Sr content described by Johnscher's universal power law in the region of high frequency.